Deletion of β-Neurexins in Mice Alters the Distribution of Dense-Core Vesicles in Presynapses of Hippocampal and Cerebellar Neurons - Shima Ferdos; Johannes Brockhaus; Markus Missler; Astrid Rohlmann (Frontiers Media S.A., 2022)
Communication between neurons through synapses includes the release of neurotransmitter-containing synaptic vesicles (SVs) and of neuromodulator-containing dense-core vesicles (DCVs). Neurexins (Nrxns), a polymorphic family of cell surface molecules encoded by three genes in vertebrates (Nrxn1-3), have been proposed as essential presynaptic organizers and as candidates for cell type-specific or even synapse-specific regulation of synaptic vesicle exocytosis. However, it remains unknown whether Nrxns also regulate DCVs. Here, we report that at least β-neurexins (β-Nrxns), an extracellularly smaller Nrxn variant, are involved in the distribution of presynaptic DCVs. We found that conditional deletion of all three β-Nrxn isoforms in mice by lentivirus-mediated Cre recombinase expression in primary hippocampal neurons reduces the number of ultrastructurally identified DCVs in presynaptic boutons. Consistently, colabeling against marker proteins revealed a diminished population of chromogranin A- (ChrgA-) positive DCVs in synapses and axons of β-Nrxn-deficient neurons. Moreover, we validated the impaired DCV distribution in cerebellar brain tissue from constitutive β-Nrxn knockout (β-TKO) mice, where DCVs are normally abundant and β-Nrxn isoforms are prominently expressed. Finally, we observed that the ultrastructure and marker proteins of the Golgi apparatus, responsible for packaging neuropeptides into DCVs, seem unchanged. In conclusion, based on the validation from the two deletion strategies in conditional and constitutive KO mice, two neuronal populations from the hippocampus and cerebellum, and two experimental protocols in cultured neurons and in the brain tissue, this study presented morphological evidence that the number of DCVs at synapses is altered in the absence of β-Nrxns. Our results therefore point to an unexpected contribution of β-Nrxns to the organization of neuropeptide and neuromodulator function, in addition to their more established role in synaptic vesicle release.